Polar solvents decrease the viscosity of high concentration IgG1 solutions through hydrophobic solvation and interaction: Formulation and biocompatibility considerations. Issue 4 (28th January 2013) - Kamerzell, Tim J.; Pace, Amanda L.; Li, Megan; Danilenko, Dimitry M.; McDowell, Michelle; Gokarn, Yatin R.; Wang, Y. John
Abstract Low‐volume protein dosage forms for subcutaneous injection pose unique challenges to the pharmaceutical scientist. Indeed, high protein concentrations are often required to achieve acceptable bioavailability and efficacy for many indications. Furthermore, high solution viscosities are often observed with formulations containing protein concentrations well above 150 mg/mL. In this work, we explored the use of polar solvents for reducing solution viscosity of high concentration protein formulations intended for subcutaneous injection. An immunoglobulin, IgG1, was used in this study. The thermodynamic preferential interaction parameter (Γ23) measured by differential scanning calorimetry, as well as Fourier transform infrared, Raman, and second‐derivative UV spectroscopy, were used to characterize the effects of polar solvents on protein structure and to reveal important mechanistic insight regarding the nature of the protein–solvent interaction. Finally, the hemolytic potential and postdose toxicity in rats were determined to further investigate the feasibility of using these cosolvents for subcutaneous pharmaceutical formulations. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:1182–1193, 2013